Folk Herbal Medicine from some Tehsils of Buldhana District (Maharashtra) in India - P.S. Patil, D.A. Patil* and (Journal of Ecobiotechnology, 2011)
The tribals and rural folks in Buldhana district sustain their healthcare on plant-based drugs for combating different ailments and disorders. They mostly belong to economically weaker sections of the society and the modern healthcare amenities are beyond their reach. The objective of the present investigation was to document ethnomedicinal claims of some notable medicinal herbs employed by the various tribal and rural folks in Buldhana district. Methodology adopted to investigate ethnomedicinal claims consist of regular field visits, gathering of data from tribal/rural people, patients and elder men/ women denizen of study area. Ethnomedicinal applications informed by at least five informants were taken into account. Present investigation revealed that people in the area studied are usually employing 58 plant species belonging to 33 families of angiosperms. They are found useful to combat as many as 35 different human health complaints. The tehsil areas studied is a treasure house of medicinal plants. These may help find out new lead molecules for human betterment. The fund of data accrued from tribal/rural people would be very useful to especially those researchers engaged in medicine. However, the fast rate of acculturation in the area reinforces the need for conservation of their traditional treasure of medicinal knowledge.